The MIDA-Q Mortality Risk Score: A Quantitative Prognostic Tool for the Mitral Valve Prolapse Spectrum. Issue 10 (27th December 2022) - Essayagh, Benjamin; Benfari, Giovanni; Antoine, Clemence; Grigioni, Francesco; Le Tourneau, Thierry; Roussel, Jean-Christian; Bax, Jeroen J.; Delgado, Victoria; Ajmone Marsan, Nina; van Wijngaarden, Aniek; Tribouilloy, Christophe; Rusinaru, Dan; et al.
Abstract : Background: Mitral valve prolapse (MVP) is responsible for a considerable disease burden but is widely heterogeneous. The lack of a comprehensive prognostic instrument covering the entire MVP spectrum, encompassing the quantified consequent degenerative mitral regurgitation (DMR), hinders clinical management and therapeutic trials. Methods: The new Mitral Regurgitation International Database Quantitative (MIDA-Q) registry enrolled 8187 consecutive patients (ages 63±16 years, 47% women, follow-up 5.5±3.3 years) first diagnosed with isolated MVP, without or with DMR quantified prospectively (measuring effective regurgitant orifice [ERO] and regurgitant volume) in routine practice of 5 tertiary care centers from North America, Europe, and the Middle East. The MIDA-Q score ranges from 0 to 15 by accumulating guideline-based risk factors and DMR severity. Long-term survival under medical management was the primary outcome end point. Results: MVP was associated with DMR absent/mild (ERO <20 mm 2 ) in 50%, moderate (ERO 20–40 mm 2 ) in 25%, and severe or higher (ERO ≥40 mm 2 ) in 25%, with mean ERO 24±24 mm 2, regurgitant volume 37±35 mL. Median MIDA-Q score was 4 with a wide distribution (10%–90% range, 0–9). MIDA-Q score was higher in patients with EuroScore II ≥1% versus <1% (median, 7 versus 3; P < 0.0001) but with wide overlap (10%–90% range, 4–11 versus 0–7) and mediocre correlation ( R 2 0.18). Five-year survival under medical management was strongly associated with MIDA-Q score, 97±1% with score 0, 95±1% with score 1 to 2, 82±1% with score 3 to 4, 67±1% with score 5 to 6, 60±1% with score 7 to 8, 44±1% with score 9 to 10, 35±1% with score 11 to 12, and 5±4% with MIDA-Q score ≥13, with hazard ratio 1.31 [1.29–1.33] per 1-point increment. Excess mortality with higher MIDA-Q scores persisted after adjustment for age, sex, and EuroScore II (adjusted hazard ratio, 1.13 [1.11–1.15] per 1-point increment). Subgroup analysis showed persistent association of MIDA-Q score with mortality in all possible subsets, in particular, with EuroScore II<1% (hazard ratio, 1.08 [1.02–1.14]) or ≥1% (hazard ratio, 1.11 [1.08–1.13]) and with no/mild DMR (hazard ratio, 1.14 [1.10–1.19]) or moderate/severe DMR (hazard ratio, 1.13 [1.10–1.16], all per 1-point increment with P <0.0001). Nested-model and bootstrapping analyses demonstrated incremental prognostic power of MIDA-Q score (all P <0.0001). Conclusions: This large, international cohort of isolated MVP, with prospective DMR quantification in routine practice, demonstrates the wide range of risk factor accumulation and considerable heterogeneity of outcomes after MVP diagnosis. The MIDA-Q score is strongly, independently, and incrementally associated with long-term survival after MVP diagnosis, irrespective of presentation, and is therefore a crucial prognostic instrument for risk stratification, clinical trials, and management of patients diagnosed with all forms of MVP.